Música sertaneja contemporânea: indústria cultural e consumo - Silva, Gabriel Barbosa Rossi da (2018)
This research aims to raise questions that problematize the production of sertanejo music in the XXI century through its trajectory as popular music in the XX century. From a historiographical point of view, this work tries to consider the bibliographical productions about the theme, placing them in the debate to contextually reach the most recent moment of sertanejo music, the "sertanejo universitário". Considering the dimension that this segment has gained from the end of the twentieth century, we will discuss the music market, what audience this music is directed to, what are its niches of production and reception, its role in the media and why it received the nickname of "universitário". Taking into consideration the trajectory of the new names of sertanejo music and their interviews to the media, we will seek to find clues in their discourses indicating the processes that has transformed such a criticized segment by specialists in the second half of the XX century, to become the most profitable Brazilian recording market, figuring the top hits of radios all over country.